Internet Financial Reporting as A Voluntary Disclosure Practice: An Empirical Analysis of Indonesian Manufacturing Firms Using Order Logit Regression - Ronny Prabowo; Johan Jimmy Carter Tambotoh (Jurnal Akuntansi dan Bisnis, 2005)
Internet Financial Reporting (IFR) is the practice of internet-based financial reporting. In financial accounting literature, IFR is regarded as a voluntary disclosure practice not because of the content of disclosure but because of the device. In this research, we investigate factors affecting the extent of IFR.. We employ independent variables usually utilized in voluntary disclosure literature (size, profitability, public ownership, foreign ownership, leverage and age). We use order logit regression (run by STATA software) because the dependent variable is ordinal and not binary. Result shows that only independent variables related to information problem (size and profitability) are significant.